Evaluation of protective immunity responses against pneumococcal PhtD and its C-terminal in combination with outer-membrane vesicles as adjuvants. Issue 3 (25th February 2020) - Malekan, Mohammadali; Siadat, Seyed Davar; Aghasadeghi, Mohammadreza; Shahrokhi, Nader; Afrough, Parviz; Behrouzi, Ava; Ahmadi, Khadijeh; Mousavi, Seyed Fazlollah
Abstract : Introduction. Streptococcus pneumoniae is a significant bacterial pathogen in humans. Currently, there are two types of pneumococcal vaccines, but there are concerns regarding their application. Aim. Since many pneumococcal proteins are serotype-independent, polyhistidine triad protein D (PhtD) has been selected as a vaccine candidate. Methodology. We prepared recombinant PhtD and its C-terminal fragment (PhtD-C) using alum and outer-membrane vesicles (OMVs) as adjuvants. The combinations were injected intraperitoneally into mice, and then total immunoglobulin G (IgG) and specific IgG, IgG1 and IgG2a were measured. A serum bactericidal assay and opsonophagocytosis were also performed as complementary tests. Meningococcal OMVs were used as an adjuvant. Results. The levels of specific IgG and IgG1 against combinations of PhtD and its C-terminal with OMVs and alum as adjuvants increased at the time of the third mouse immunization on day 35. Forty per cent and 60% of S. pneumoniae ATCC 6303 (serotype 3) as a virulent pneumococcal strain, respectively, were killed in the opsonophagocytosis test and these results could also be observed in the serum bactericidal assay. Mice mmunized iwith PhtD and its C-terminal with OMVs and alum as adjuvants survived after 10 days of pneumococcal challenge. Conclusion. The combination of PhtD and PhtD-C with alum produced optimal results, but the combination of PhtD and PhtD-C with OMVs produced minimal results by comparison. The survival rates were also measured, and these corresponded with the results of the immunological assessments. Our findings showed that mice receiving PhtD and PhtD-C plus OMV and alum had higher survival rates than the mice in the other groups.